2014
DOI: 10.2139/ssrn.2456580
|View full text |Cite
|
Sign up to set email alerts
|

Innovation by Patients with Rare Diseases and Chronic Needs

Abstract: We provide the first empirical exploration of disease-related innovation by patients and their caregivers. Our aims were to explore to what degree do patients develop innovative solutions; how many of these are unique developments; and do these solutions have positive perceived impact on the patients' overall quality of life? In addition, we explored the factors associated with patient innovation development, and sharing of the solutions that the patients developed. Methods: We administered a questionnaire via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 26 publications
(15 reference statements)
2
39
0
1
Order By: Relevance
“…In higher income countries, consumer innovation represents a significant portion of a nation's innovation activities (Bengtsson 2015;De Jong 2011;Kuusisto et al 2013;Ogawa and Pongtanalert 2011;von Hippel, de Jong, and Flowers 2012). Examples are wide-ranging, including children's products developed by parents (Shah and Tripsas 2007), software and sport-related goods (Jeppesen and Frederiksen 2006;Lüthje 2004), and therapies for chronic diseases (Oliveira et al 2015). But examples also exist from communities in poorer situations, where bottom-up innovations may contribute not only to the development of new technologies, but also to social empowerment, like the case of sanitary solutions in India (Kumar and Bhaduri 2014).…”
Section: Civil Society Engagement and Bottom-up Innovationmentioning
confidence: 99%
“…In higher income countries, consumer innovation represents a significant portion of a nation's innovation activities (Bengtsson 2015;De Jong 2011;Kuusisto et al 2013;Ogawa and Pongtanalert 2011;von Hippel, de Jong, and Flowers 2012). Examples are wide-ranging, including children's products developed by parents (Shah and Tripsas 2007), software and sport-related goods (Jeppesen and Frederiksen 2006;Lüthje 2004), and therapies for chronic diseases (Oliveira et al 2015). But examples also exist from communities in poorer situations, where bottom-up innovations may contribute not only to the development of new technologies, but also to social empowerment, like the case of sanitary solutions in India (Kumar and Bhaduri 2014).…”
Section: Civil Society Engagement and Bottom-up Innovationmentioning
confidence: 99%
“…In a preceding study by Lüthje (2003) in the healthcare sector, 22% of the participating surgeons were innovating. Oliveira et al (2015) found that 36% of all patients with a chronic condition or their relatives innovated in relation to their needs. These findings are in line with a growing body of literature that indicates that patients are gaining increased medical expertise in relation to their disease (Budych et al 2012;Hartzler and Pratt 2011;Greenhalgh 2009;Thorne et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have only recently identified the innovative potential of patients and relatives (Oliveira et al 2015;Habicht et al 2013;Bullinger et al 2012). Regarding the shift to chronic diseases, patients are acting increasingly proactively and are becoming experts in their health issues.…”
Section: User Innovation In Healthcarementioning
confidence: 99%
See 2 more Smart Citations